Recent Advances in Perovskite Oxides as Electrode Materials for Nonaqueous Lithium-Oxygen Batteries - Tan, P.; Liu, M.; Shao, Zongping; Ni, M. (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim., 2017)
Lithium-oxygen batteries are considered the next-generation power sources for many applications. The commercialization of this technology, however, is hindered by a variety of technical hurdles, including low obtainable capacity, poor energy efficiency, and limited cycle life of the electrodes, especially the cathode (or oxygen) electrode. During the last decade, tremendous efforts have been devoted to the development of new cathode materials. Among them, perovskite oxides have attracted much attention due to the extraordinary tunability of their compositions, structures, and functionalities (e.g., high electrical conductivities and catalytic activities), demonstrating the potential to achieve superior battery performance. This article focuses on the recent advances of perovskite oxides as the electrode materials in nonaqueous lithium-oxygen batteries. The electrochemical mechanisms of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) on the surface of perovskite oxides are first summarized. Then, the effect of nanostructure and morphology on ORR and OER activities is reviewed, from nanoparticles to hierarchical porous structures. Moreover, perovskite-oxide-based composite electrodes are discussed, highlighting the enhancement in electrical conductivities, catalytic activities, and durability under realistic operating conditions. Finally, the remaining challenges and new directions for achieving rational design of perovskite oxides for nonaqueous lithium-oxygen batteries are outlined and discussed.